STIMULASI KEMAMPUAN BERBICARA MELALUI MEDIA WAYANG KARDUS PADA ANAK USIA 5-6 TAHUN - Dyah Hesti Kusmawarni; Febru Puji Astuti; Khusnul Laely; Reza Edwin Sulistyaningtyas (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
The social environment provides its own challenge for the child’s development phase, especially in communicating verbally or speaking. This ability can also affect a child's performance at school. However, there are still many children who have less ability to speak, so this study aims to determine the stimulation of speaking ability with wayang cardboard media in children aged 5-6 years at Kindergarten ABA 5 Ganjuran. Subjects in the study were 5-6 years old, totaling 16 children, consisting of 7 boys and 9 girls. This Classroom Action Research was conducted in three cycles and each cycle was conducted in three meetings. The results of the research conducted show that shildren’s speaking ability can be improved through the application of the storytelling method. This is proven by the increase in the results of the assessment in each cycle, the ability to speak at pre-action reached 12% good, and in cycle I it increased to 19% well, the ability to speak in cycle II was 44% good and in cycle III it increased to 81.25% good . The conclusion from this classroom action research is that the storytelling method can improve the speaking skills of the children in the ABA 5 Ganjuran Kindergarten group. Keywords: early childhood education, storytelling, speaking ability